2023
DOI: 10.3390/mi14030617
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Self-Healing Conductive Elastomers for Modular Assembly as a Microfluidic Electrochemical Biosensing Platform for the Detection of Colorectal Cancer Exosomes

Abstract: Modular components for rapid assembly of microfluidics must put extra effort into solving leakage and alignment problems between individual modules. Here, we demonstrate a conductive elastomer with self-healing properties and propose a modular microfluidic component configuration system that utilizes self-healing without needing external interfaces as an alternative to the traditional chip form. Specifically, dual dynamic covalent bond crosslinks (imine and borate ester bonds) established between Polyurethane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A different study found that immunoaffinity isolation using anti-CD9 conjugated, anti-CD81, and antibody cocktail-linked magnetic nanowires magnetic beads could achieve a yield that was almost three times higher than that of classical approaches. In comparison to results obtained using more traditional approaches, Tim4, which binds exclusively to the phosphatidylserine on the surface of exosome cells, shown much less contamination [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…A different study found that immunoaffinity isolation using anti-CD9 conjugated, anti-CD81, and antibody cocktail-linked magnetic nanowires magnetic beads could achieve a yield that was almost three times higher than that of classical approaches. In comparison to results obtained using more traditional approaches, Tim4, which binds exclusively to the phosphatidylserine on the surface of exosome cells, shown much less contamination [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…195 Electrochemical sensors for microorganisms using MXene-based nanomaterials are summarized in Table 4. Exosomes, [196][197][198][199] bacteria, [200][201][202][203][204][205] viruses, 149,[206][207][208][209] and even cancer cells 114,171 can be measured through appropriate surface modification of electrodes. The lowest sensing range is about 10 particles per mL.…”
Section: The Applications Of Mxenes In Microorganism Sensorsmentioning
confidence: 99%
“…The constructed microfluidic electrochemical biosensing platform enabled the detection of exosomes indicative of colorectal cancer over a wide detection range (50-10 5 particles μL −1 ) with a low LOD (42 particles μL −1 ), making it a disposable, reusable, costeffective, and rapid analysis platform. [188] Son et al created a selfhealable and conductive ink by incorporating graphene into the self-healing polymer poly(1,4-cyclohexanedimethanol succinateco-citrate), with the printed serpentine-structured electrode exhibiting good conductivity while spontaneously healing during 10 cut-heal cycles with a healing time of just 12 s at ambient conditions while retaining a sensitivity of 99% for detecting Na + in sweat in real time. [189] The incorporation of antifouling hydrogels within these of similar self-healing coatings thus offers potential, particularly in designing wearable and implantable sensors with enhanced performance.…”
Section: Self-healingmentioning
confidence: 99%